EFEKTIVITAS PENGGUNAAN TEKNOLOGI INFORMATIKA DALAM MENINGKATKAN PELAYANAN PERPUSTAKAAN UMUM DAERAH KABUPATEN SIDENRENG RAPPANG - Asri Rahayu; Nurjannah Nonci; Erfina Erfina; Jamaluddin Ahmad; Andi Nilwana (LPPM Universitas Abdurrab, 2026)
This study analyzes the effectiveness of information technology in improving services at the Sidenreng Rappang Regency Public Library using a descriptive qualitative approach. Data were collected through in-depth interviews with librarians and library users, observation, and documentation, analyzed using the Miles and Huberman model. Results show that Inlislite, SIDEREAD, and OPAC systems improved service speed from 10 minutes to 1-2 minutes per transaction, enhancing operational efficiency and transparency. However, utilization remains low (25% of active members) due to low digital literacy, limited internet infrastructure in rural areas, uneven digital skills among librarians, and minimal socialization. Optimization strategies include continuous librarian training, infrastructure strengthening, community-based literacy programs, and integration with the iPusnas platform. This study contributes to understanding library digitalization implementation at the regency level by considering local socio-cultural characteristics.